2017
DOI: 10.1186/s12971-017-0151-x
|View full text |Cite
|
Sign up to set email alerts
|

Are political views related to smoking and support for tobacco control policies? A survey across 28 European countries

Abstract: BackgroundGeneral political views are rarely considered when discussing public support for tobacco control policies and tobacco use. The aim of this study was to explore potential associations between political views, smoking and support for tobacco control policies.MethodsWe analysed responses from 22,313 individuals aged ≥15 years from 28 European Union (EU) member states, who self-reported their political views (far-left [1–2 on a scale 1–10]; centre-left (3-4); centre (5-6); centre-right (7-8); and far-rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
12
2
Order By: Relevance
“…Support for price increases varies: whereas the English public seems to agree with tax increases [ 39 ], support in European countries with lower GDPs has declined in past years [ 49 ]. Our results do not show associations with socio-demographic characteristics, yet a recent study by Filippidis et al [ 52 ] raises the possibility of associations between political views and support for tobacco control. Further insights into reasons behind these variations by European country might be useful for coherent European tobacco control strategies.…”
Section: Discussioncontrasting
confidence: 99%
“…Support for price increases varies: whereas the English public seems to agree with tax increases [ 39 ], support in European countries with lower GDPs has declined in past years [ 49 ]. Our results do not show associations with socio-demographic characteristics, yet a recent study by Filippidis et al [ 52 ] raises the possibility of associations between political views and support for tobacco control. Further insights into reasons behind these variations by European country might be useful for coherent European tobacco control strategies.…”
Section: Discussioncontrasting
confidence: 99%
“…This type of policy is stricter than the current legislation. In addition, one position would face most people's opposition: Low-levels of regulation (blood alcohol limit of 0.8 g/l, no control of selling points, and sale allowed to 16 year-olds) associated with an absence of prevention measures and a low-level of sanctions. This finding echoes those of previous studies showing that the general public in the United Kingdom and Australia were both more favorable towards alcohol policies with greater enforcement of sanctions (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…As for tobacco control policies, it has been found that non-smokers, ex-smokers, women, older participants, and participants with non-conservative political views were more supportive of them than smokers, men, younger participants, and participants with conservative views [15][16][17][18]. The impact of educational and socio-economic level on support has, however, been more difficult to assess [19].…”
mentioning
confidence: 99%
“…With respect to political orientation, we found that individuals who identified as liberal were significantly more likely to support most policies, which is consistent with research estimating support for other tobacco control initiatives. 47,48 However, it is important to note that estimates of support across policies were high regardless of political ideology. Collectively, these results provide strong evidence that the American public-regardless of region, political ideology, and existing policy environments-are in favor of advancing e-cigarette related policies.…”
Section: Discussionmentioning
confidence: 99%